Advancing Organizational Sustainability through Responsible Innovation and Green Human Resource Management: Evidence from Indonesia’s Public Sector - Silveny Ismail; Fahrudin Zain Olilingo; Raflin Hinelo; Robiyati Podungge (Journal of International Conference Proceedings, 2026)
Public-sector organisations in developing countries face increasing pressure to achieve sustainability through responsible innovation and environmentally oriented human resource management practices. This study investigates the direct effect of Responsible Innovation Practices (RIP) on Organisational Sustainability (OS) and the indirect effect through Green Human Resource Management (GHRM) among Indonesian public-sector employees. A quantitative causal-explanatory approach was employed using survey data from 300 civil servants, analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that RIP has a significant positive effect on both GHRM and organisational sustainability. GHRM also positively influences organisational sustainability and partially mediates the relationship between RIP and sustainability, indicating that responsible innovation strengthens sustainable outcomes through environmentally oriented HRM practices. These results suggest that public organisations should integrate responsible innovation into recruitment, training, performance management, and reward systems. This study contributes to the sustainability and HRM literature by providing empirical evidence from Indonesia's public sector and highlighting the strategic role of green HRM in achieving organisational sustainability